Effects of NextGen Concepts of Operation for Separation Assurance and Interval Management on Air Traffic Controller Situation Awareness, Workload, and Performance. Issue 1 (2nd April 2016) - Strybel, Thomas Z.; Vu, Kim-Phuong L.; Chiappe, Dan L.; Morgan, Corey A.; Morales, Gregory; Battiste, Vernol
ABSTRACT: Objective : Determine how combinations of NextGen-automation concepts for separation assurance and spacing affect air traffic controller (ATCo) situation awareness, workload, and performance. Background : In previous research, situation awareness was not measured with valid and reliable instruments. Previous work also evaluated separation assurance and spacing concepts individually, and did not examine weather. Method : Retired ATCos worked en route and transitional sectors. Four operating concepts for separation assurance and spacing were tested based on whether automation or ATCo was responsible for each function. Standard methods for assessing workload and situation awareness were used; performance measures included safety and efficiency. Results : Workload was lowest when both functions were automated; however, situation awareness depended on operating concept and sector. In the en route sector, the highest levels of situation awareness were found for ATCo-managed separation assurance and automation-managed spacing. In the transitional sector, the highest situation awareness occurred when ATCos performed both functions. The numbers of loss of separation were highest for ATCo-managed separation assurance; sector complexity depended on weather, but only for automation-managed separation assurance. Spacing efficiency was highest for ATCo-managed separation assurance, but more communications were required. Conclusion : In air traffic management, separation assurance and spacing functions interact with each other in determining ATCo workload, situation awareness, and performance, depending on sector characteristics and weather. Therefore, evaluations of NextGen-automation solutions must include multiple concepts of operation, and involve different sectors and environmental conditions.